Islands apart: leadership studies in two island states - Billot, J (Taylor & Francis, 2005)
School leadership is situated within a context of social and political factors that work to distribute power while also holding it in check. There are connections between how societal political structures facilitate democratic participation and the operation of schools. Educational leadership straddles the interface between proactive agency and the politics of social control. This tension between holding and using authority, yet acceding to political and social practice, is one which many school leaders face. Research studies conducted in two island nations, Jersey (Channel Islands) and Tonga (Pacific Islands), in different hemispheres of the world, illustrated contrasting forms of educational service and different challenges for school principals. As island communities, the context was clearly definable and provided a set of variables that were manifested through sector processes. The principals held pivotal roles that were molded by the contextual factors which shaped the delivery of educational practice. School principals in Jersey and Tonga illustrated how leadership is complicated if the purposes leadership should serve are unclear or contested (O'Brien, Murphy, and Draper 2003).